Retirement preparedness and subjective well-being: Evidence from Malaysia - Guptan, Vinitha; Ratneswary, Rasiah; Harpaljit Kaur, Pritam Singh; Turner, Jason James; Kumar, Senthil; Sorooshian, Shahryar (Romanian Society for Quality Assurance - SRAC, 2021)
Organizations offer sufficient preparation to prepare their employees to succeed at work, but very few, if any, prepare their employees for life after work. A cross-sectional survey was undertaken, with a total of 514 Malaysian employees participating in the study. The Partial Least Squares-Structural Equation Modelling estimation technique was employed to analyse the data. The results revealed that retirement preparedness in orgnizations via financial knowledge, retirement goals and retirement confidence significantly enhances subjective well-being of employees. The study serves to discuss current policy issues that affect the government, financial institutions, the employees, the elderly and their families.